PREGNANCY AND DENTAL HEALTH: NAVIGATING THE COMPLEXITIES OF ORAL CARE, RISKS AND PREVENTIVE APPROACHES FOR EXPECTANT MOTHERS - Ciprian Gavrila Ilea; Irina Liviana Stoian; Alexandra Pangal; Bogdan Doroftei; Adeline Samar Nassouh; Laurian Lucian Francu; Corina Ciupilan; Monica Mihaela Scutariu (Romanian Journal of Oral Rehabilitation)
Pregnancy introduces significant physiological and hormonal changes that can impact oral health, increasing the risk of conditions such as gingivitis, periodontitis, dental caries, and enamel erosion. These oral health issues, if left untreated, may contribute to adverse pregnancy outcomes, including preterm birth and low birth weight. Despite the critical role of oral health in pregnancy, many expectant mothers face barriers such as lack of awareness, financial constraints, and limited access to dental services, which hinder timely intervention. This review explores the common oral health challenges faced by pregnant women, their potential impact on maternal and fetal well-being, and the barriers that prevent access to adequate care. Additionally, it highlights preventive strategies, including improved oral hygiene practices, early detection, and the integration of dental care into routine prenatal healthcare. Emerging technological advancements, such as artificial intelligence and teledentistry, are also discussed as potential tools to enhance accessibility and diagnostic accuracy in maternal oral healthcare. The review concludes by emphasizing the need for a multidisciplinary approach that involves collaboration between dental and prenatal care providers to ensure comprehensive healthcare for expectant mothers. Increased awareness, policy changes, and public health initiatives are essential to promoting better oral health outcomes and reducing healthcare disparities among pregnant women.